Molecular characterization of environmental Cladosporium species isolated from Iran - Ilnaz Ghiaie Asl; Marjan Motamedi; Gholam Reza Shokuhi; Nilufar Jalalizand; Armin Farhang; Hossein Mirhendi (Mazandaran University of Medical Sciences, 2017)
Background and Purpose: Cladosporium species are ubiquitous, saprobic,dematiaceous fungi, only infrequently associated with human and animal opportunisticinfections. Materials and Methods: Airborne samples were collected using the settle plate method, and soil samples were obtained from a depth of 5-10 cm of the superficial soil layer. Samples were cultured on Sabouraud dextrose agar (SDA) plates, incubated at 25°C, and examined daily for fungal colonies for two to three weeks. Isolates were identified as Cladosporium species according to the macroscopic and microscopic criteria. For species differentiation, DNA from 53 isolates was extracted and subjected to amplification of the internal transcribed spacer (ITS) region followed by sequencing. Results: A total of 270 samples were collected from various environmental sources, of which 79 strains of Cladosporium species were isolated. The most frequent species was C. cladosporioides (50.6%), followed by C. iridis (44.3%), C. elatum (2.5%), C. peranqestum (1.3%), and C. alicinum. (1.3%). Conclusion: The collected data can serve as baseline information for future research and may be useful in the development of preventive and educational strategies.